On a couple-stress Rivlin-Ericksen ferromagnetic fluid heated from below with varying gravity, rotation, magnetic field and suspended particles flowing through a porous medium - Rahul; Sharma, Naveen (Zielona Góra: Uniwersytet Zielonogórski)
The thermal instability of a couple-stress Rivlin-Ericksen ferromagnetic fluid with varying gravity field, suspended particles, rotation and magnetic field flowing through a porous medium is investigated. The dispersion relation has been developed and solved analytically using the normal mode approach and linear stability theory. The effect of suspended particles, rotation, couple stress, permeability and magnetic field on the fluid layer has been investigated.
Keywords: thermal instability; magnetic field; couple-stress fluid; ferromagnetic fluid; suspended particles